Call to action: how can the US Ending the HIV Epidemic initiative succeed?. Issue 10279 (20th March 2021) - Beyrer, Chris; Adimora, Adaora A; Hodder, Sally L; Hopkins, Ernest; Millett, Greg; Mon, Sandra Hsu Hnin; Sullivan, Patrick S; Walensky, Rochelle P; Pozniak, Anton; Warren, Mitchell; Richman, Bruce; Copeland, Raniyah; et al.
Summary: With more than 1·2 million people living with HIV in the USA, a complex epidemic across the large and diverse country, and a fragmented health-care system marked by widening health disparities, the US HIV epidemic requires sustained scientific and public health attention. The epidemic has been stubbornly persistent; high incidence densities have been sustained over decades and the epidemic is increasingly concentrated among racial, ethnic, and sexual and gender minority communities. This fact remains true despite extraordinary scientific advances in prevention, treatment, and care—advances that have been led, to a substantial degree, by US-supported science and researchers. In this watershed year of 2021 and in the face of the COVID-19 pandemic, it is clear that the USA will not meet the stated goals of the National HIV/AIDS Strategy, particularly those goals relating to reductions in new infections, decreases in morbidity, and reductions in HIV stigma. The six papers in the Lancet Series on HIV in the USA have each examined the underlying causes of these challenges and laid out paths forward for an invigorated, sustained, and more equitable response to the US HIV epidemic than has been seen to date. The sciences of HIV surveillance, prevention, treatment, and implementation all suggest that the visionary goals of the Ending the HIV Epidemic initiative in the USA might be achievable. However, fundamental barriers and challenges need to be addressed and the research effort sustained if we are to succeed.